Loyalitas Karyawan pada Universitas Swasta di Kota Bengkulu - Onsardi Onsardi (COSTING : Journal of Economic, Business and Accounting, 2018)
Loyalty in an organization is an important element in supporting the success of human resources in achieving company goals. This study aims to analyze employee loyalty in Private Universities in Bengkulu City and the factors that influence it. This study uses a quantitative approach with survey methods. The population of this study were all private university employees in the city of Bengkulu, amounting to 305 people, from a total population of 173 people with proportional ramdom sampling technique .The data analysis technique used is descriptive and inferential analysis. The results of this study prove that (1) employee loyalty is still relatively low (2) there is a positive and significant direct influence of compensation, empowerment and job satisfaction variables on employee loyalty, (3) There is a positive and significant direct effect of compensation and empowerment variables on job satisfaction, (4) There is a positive and significant direct effect of compensation variables on empowerment. Keywords: Loyalty, Compensation, Empowerment, and Job Satisfaction.